2016
DOI: 10.1007/s10900-016-0225-3
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to Pap Smear Follow-up among Women in the Criminal Justice System

Abstract: Women involved in the United States criminal justice system face a variety of challenges in maintaining their health. Histories of sexual abuse, early initiation of sex, and substance abuse are reflected in more negative reproductive health outcomes, including cervical cancer, than those found among non-incarcerated women. Little is known about how to close this health gap. The present study assessed what incarcerated women perceived to be facilitators and inhibitors of obtaining recommended follow-up for abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Incarcerated women have uniquely complicated barriers when it comes to cervical health literacy – specifically, complex risk histories and environments that may affect their ability to act on knowledge about cervical health. For example, one barrier to knowledge stems from frequent STI checks, which inadvertently cause confusion over pelvic and Pap screening ( Kelly et al, 2017 ). Furthermore, these women's long trauma histories tend to impact on their beliefs about Pap screening – that is, an expectation of fear, discomfort, and questionable safety during gynecological exams ( Ramaswamy & Kelly, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Incarcerated women have uniquely complicated barriers when it comes to cervical health literacy – specifically, complex risk histories and environments that may affect their ability to act on knowledge about cervical health. For example, one barrier to knowledge stems from frequent STI checks, which inadvertently cause confusion over pelvic and Pap screening ( Kelly et al, 2017 ). Furthermore, these women's long trauma histories tend to impact on their beliefs about Pap screening – that is, an expectation of fear, discomfort, and questionable safety during gynecological exams ( Ramaswamy & Kelly, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The findings of this study are consistent with another study of incarcerated women in the Kansas City area that found Pap tests were often thought of as an all-inclusive screening for gynecological and pelvic health issues. Pelvic exam findings such as abnormal bleeding, STIs, bacterial vaginosis, yeast infections, and ovarian cysts were considered “abnormal Pap test results” by many of the women in interviews [8].…”
Section: Discussionmentioning
confidence: 99%
“…Limited cervical health literacy may lead women to mistakenly report a pelvic exam as a Pap test [7]. Cervical cancer screening awareness among justice-involved women is low, with studies showing that incarcerated women consider any range of women’s health problems as “abnormal Pap test results,” and confusion about the etiology of cervical cancer, screening recommendations, and need for screening [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Following release from jail or prison, criminal-legal involved women encounter significant barriers to cervical care-they must obtain health insurance and find a primary care provider, while also securing income, housing, food, and other basic needs [8,14,15]. Barriers that limit access to preventive cervical care have been well studied, but there are less data on factors that will facilitate abnormal Pap follow-up.…”
Section: Introductionmentioning
confidence: 99%